Occupational diseases in Poland in 2016 - Beata Świątkowska; Wojciech Hanke (Nofer Institute of Occupational Medicine, 2018)
Background The aim of the work is to present the epidemiological situation in the field of occupational diseases in Poland in 2016. Material and Methods The cases of occupational diseases identified in accordance with the applicable case law system in Poland and reported to the Central Register of Occupational Diseases in 2016 were analyzed. The analysis includes nosologic units, their causative factors as well as gender and age of patients. Absolute numbers and incidence rates per 100 000 employees were presented. Results In 2016, 2119 cases of occupational diseases were recorded in Poland, i.e. 14.3 cases per 100 000 employed persons. The incidence rate was mainly caused by pneumoconioses (28.5%), infectious or parasitic diseases (27.2%), chronic voice disorders (9.7%), chronic diseases of the peripheral nervous system (8.6%) and hearing loss (6.3%). The highest incidence was recorded in the mining and quarrying (329.7 cases), agriculture and forestry (23.8 cases), manufacturing (20 cases) and education (17.9 cases) and healthcare and social work activities (17.7 cases). Conclusions In comparison with 2015, there was an increase in the number of cases of occupational diseases by 1.2%, which was influenced mainly by a larger (by 181 cases) number of pneumoconiosis. The epidemiological situation resulting from occupational diseases in our country, although it covers all identified cases, should be assessed with caution because the suspicion arises underestimation of certain diseases, especially cancer. Med Pr 2018;69(6):643-650